SELF-CONCEALMENT IN JEAN WEBSTER’S DADDY LONG LEGS - Fania Hasri Fitranti; Mamik Tri Wedawati (Elite : English and Literature Journal, 2021)
This research studied the self-concealment of the main character in Daddy Long Legs novel. It is aimed at identifying self-concealment through the main character’s Johari Windows. This research also described fear of self-disclosure. The method used is descriptive-qualitative research This analysis is collaborating the concept of self-concealment with Johari Window. The results showed, Judy Abbott, the main character does self-concealment which is identified by the most dominated hidden area in her Johari Window which is including fear of self-disclosure. By comparing with previous self-concealment analysis in some literary studies, it is found that self-concealment is connected with queerness, deception, and either repression or suppression defense mechanism.